The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/famp.12195
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Functional Family Therapy in Reducing Adolescent Mental Health Risk and Family Adjustment Difficulties in anIrish Context

Abstract: To evaluate the effectiveness of Functional Family Therapy (FFT) 42 cases were randomized to FFT and 55 to a waiting-list control group. Minimization procedures controlled the effects of potentially confounding baseline variables. Cases were treated by a team of five therapists who implemented FFT with a moderate degree of fidelity. Rates of clinical recovery were significantly higher in the FFT group than in the control group. Compared to the comparison group, parents in the FFT group reported significantly g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
2
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 39 publications
5
36
2
9
Order By: Relevance
“…In another study, based at the same site, Hartnett et al . () found that improvements shown via SDQ were sustained at three‐month follow‐up.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In another study, based at the same site, Hartnett et al . () found that improvements shown via SDQ were sustained at three‐month follow‐up.…”
Section: Literature Reviewmentioning
confidence: 97%
“…In addition to these validation studies, in two controlled trials, improvements occurred on the SCORE‐28 in the treatment group, but not in the control group (Cassells et al., ; Hartnett, Carr, & Sexton, ). In a study of the Polish SCORE‐15, this instrument was found not to be sensitive to therapeutic change over three sessions in the context in which it was evaluated.…”
Section: Overall Findingsmentioning
confidence: 99%
“…Positive findings, in the form of reduced reoffending rates, have been reported in Norway (Thøgersen, ), and Sweden (Hansson, Cederblad, & Höök, ). Two studies in Ireland (Graham, Carr, Rooney, Sexton, & Wilson Satterfield, ; Hartnett, Carr, & Sexton, ) reported success in implementation, as well as significant, sustained reductions in youth behavioral problems. However, a recent RCT conducted in the United Kingdom did not find any differences in reoffending rates or self‐reported delinquency between youth who received FFT, relative to those in a comparison group (Humayun et al., ).…”
Section: Family Functioning and Youth Offendingmentioning
confidence: 99%